Analisis Dampak Penggunaan Konten AI-Generated terhadap Kinerja Pemasaran Online UMKM Mahasiswa Solo dalam Mata Kuliah Digital Marketing - Fahrurozi, Slamet Kurniawan; Epin Andrian, Dimas Pamilih; Rachmawati, Annisa Noor (Lembaga Yasin AlSys, 2025)
The limited research on the use of AI-generated content (AIGC) in digital marketing education within vocational settings forms the background of this study, despite AIGC’s significant potential to transform how students design promotional strategies and carry out online selling activities. This study aims to analyze how students perceive the use of AIGC and its impact on online sales performance in the context of a Digital Marketing course. A qualitative approach with a case study design was employed, involving eight participants selected through purposive sampling. Data were collected via semi-structured interviews and analyzed using thematic analysis. The findings reveal that AIGC supports content production efficiency, enhances audience engagement, and expands students’ digital reach. However, its impact on sales performance remains inconsistent due to external factors such as market segmentation and distribution strategies. These findings align with social-cognitive learning theory, which emphasizes the role of direct experience in the learning process. The study concludes that AIGC plays a crucial role in supporting project-based learning in vocational education, particularly in the context of digital entrepreneurship. The implications include a theoretical contribution to the literature on AI integration in vocational education, as well as practical recommendations for educators to adapt curricula that are responsive to technological advancements. This research also opens avenues for further studies on the long-term effectiveness of AIGC in enhancing students’ digital business performance.